Distribution of Acute Respiratory Infection (ARI) Disease Findings in Toddlers in Central Sulawesi Province, Indonesia, 2023 - aan, galang; adrian (Yayasan Cipta Anak Bangsa (YCAB) Publisher, 2026)
Background: Acute Respiratory Infection (ARI) is one of the main causes of death and morbidity in children under five, especially in developing countries such as Indonesia. ARI is greatly influenced by various factors, such as the living environment, nutritional status of children, immunization, and family behavior and knowledge in preventing disease. Central Sulawesi as one of the provinces in Indonesia still faces challenges in controlling this disease. Objective: This study aims to describe the distribution of ARI case findings in toddlers in Central Sulawesi Province in 2023 and to analyze the achievement of national targets. Method: This study uses a descriptive quantitative approach with secondary data obtained from the Health Profile of Central Sulawesi Province in 2023. The analysis was carried out using descriptive techniques to describe the scope of pneumonia case findings in toddlers in all districts/cities. Results: The results of the study showed that the coverage of pneumonia findings in toddlers in Central Sulawesi Province in 2023 was only 55.8%, still far below the national target of 75%. Only 5 out of 13 districts/cities managed to achieve this target. The low coverage of case finding is closely related to unhealthy environmental factors, low family knowledge about preventing ARI, and risk behavior such as smoking in the home. Conclusion: Efforts to control ARI in toddlers need to be focused on increasing early detection, improving the quality of housing and the environment, and public health education. Cross-sector interventions are very important to reduce morbidity and mortality due to ARI, especially in areas with low case finding coverage.